1,2,4-Triazole Schiff base directed synthesis of polynuclear iron complexes: Investigating the magnetic properties going from a dimer to a 1D chain to a 3D framework - Li, Ai-Min; Rentschler, Eva (Polyhedron, 2018)
Based on two functionalized Schiff base ligands 4-(1H-imidazol-5-ylmethylene-amino)-4H-1,2,4-triazole (imztrz) and 4-(p-tolylidene-amino)-4H-1,2,4-triazole (toltrz), a series of three triazole based polynuclear Fe complexes has been prepared. Compounds [FeII(toltrz)2(C2O4)]·10H2On (1) and [FeII(5-imztrz)(C2O4)]·2H2On (2) are oxalate bridged FeII complexes with 1 showing a linear 1D chain structure and 2 exhibiting a zigzag chain based 3D interpenetrating framework. Both structures show rather big voids in the 3D architecture (∼15% of the crystal volume). Compound (5-imztrzH)2[FeIII 2(cit4−)2(H2O)2]·6H2O (3) is a binuclear FeIII complex bridging by two citrate ligands to form a face-shared centrosymmetric structure. Magnetic susceptibility measurements indicate that all three compounds show weak antiferromagnetic exchange interaction between the adjacent Fe centers.
CRIS-Team Scopus Importer:2023-03-27
Keywords: 1; 2; 4-Triazole; Iron; Polynuclear; Schiff bases; Supramolecular Framework